A Pseudo-Distance Algorithm for Collision Detection of Manipulators Using Convex-Plane-Polygons-based Representation. (December 2020) - Xu, Jingjing; Liu, Zhifeng; Yang, Congbin; Li, Longfei; Pei, Yanhu
Highlights: A pseudo-distance algorithm for collision detection of manipulators is proposed. Convex-Plane-Polygons-based representation is firstly introduced. Results show the algorithm can largely improve the efficiency of collision detection. This algorithm are applicable to both convex and nonconvex objects. Abstract: Robots have become indispensable parts for the industrial automated workshop. The distance calculation between the industrial robot and obstacles is a fundamental problem for the robotic collision-free motion control. But existing methods for this problem have the disadvantage that the accuracy and execution efficiency cannot be guaranteed at the same time. In this paper, a pseudo-distance algorithm is presented based on the convex-plane-polygons-based representation to solve this problem. In this algorithm, convex plane polygons (CPPs) and cylinders are utilized to represent obstacles and the manipulator, respectively. The spatial relationship between each CPP and each cylinder is discussed through defining condition parameters, and is divided into six conditions including three special conditions when the contact happens, and the other three conditions when there exists a certain distance between the CPP and the cylinder. The distance is modelled under different relations based on the theory of mathematics and geometry. The pseudo distance is determined through selecting the smallest value from distances between CPPs and cylinders. The numerical experiment is performed based on the proposed and two previous algorithms to estimate the shortest distance between an industrial robot and a groove-shape obstacle. And an application example is performed to show the significance of this work on the robotic motion control. Results indicate that the proposed algorithm is more efficient than previous algorithms under a certain precision requirement, and can be effectively applied in the robotic motion control.